Coping with Water Deficiency From Research to Policymaking With Examples from Southern Europe, the Mediterranean and Developing Countries - Koundouri, Phoebe; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
In line with the Water Framework Directive, this book stresses the need for an Integrated Water Resources Management (IWRM) approach to balance the competing demands on water-domestic, agricultural, industrial, tourism and environmental/ecological- and promote economically efficient, socially equitable and environmentally sustainable water use in selected regions from Southern Europe, the Mediterranean and the developing world. Results from the research projects covered by this book, demonstrate that effective water management tools and decisions-making practices, are needed in order to complement integrated interventions for increasing the availability of supply and/or managing the growing demand for scarce water supplies. Further, the book attempts to bridge the gap between ideas and actions endorsed at the research-oriented environmental debate, and their translation into policy making structures and programs in developed and developing countries.
Results from the ARID Cluster and other European Research Projects -- Water Management on Mediterranean Islands: Pressure, Recommended Policy and Management Options -- The Range of Existing Circumstances in the WaterStrategyMan Case Studies -- Landscape Sensitivity, Resilience and Sustainable Watershed Management -- Using Economic Valuation Techniques to Inform Water Resources Management in the Southern European, Mediterranean and Developing Countries: A Survey and Critical Appraisal of Available Techniques -- The Case for Declining Long-Term Discount Rates in the Evaluation of Flood-Defence Investments -- Models and Decisions Support Systems for Participatory Decision Making in Integrated Water Resource Management -- Results from the Developing World -- Evaluating the Institution-Impact Interactions in the Context of Millennium Development Goals -- Resource Pricing and Poverty Alleviation: The Case of Block Tariffs for Water in Beijing.
Keywords: ECONOMICS; ENVIRONMENTAL POLLUTION; ENVIRONMENTAL ECONOMICS; SOCIAL SCIENCES; ECONOMICS/MANAGEMENT SCIENCE; ENVIRONMENTAL ECONOMICS; WASTE WATER TECHNOLOGY / WATER POLLUTION CONTROL / WATER MANAGEMENT / AQUATIC POLLUTION; SOCIAL SCIENCES, GENERAL